Drilling Waste Disposal and Public Health in Oil-Producing Communities: A Comprehensive Review - Benson-Ubochi Chibueze (IIARD INTERNATIONAL JOURNAL OF GEOGRAPHY AND ENVIRONMENTAL MANAGEMENT, 2026)
The rapid expansion of global oil and gas exploration has generated substantial quantities of hazardous drilling waste, presenting a major environmental and public health challenge, particularly in resource-rich developing nations. Drilling waste—comprising spent drilling muds, drill cuttings, produced water, chemical additives, and operational sludges—contains a complex mixture of toxic constituents, including polycyclic aromatic hydrocarbons (PAHs), heavy metals (lead, cadmium, chromium, arsenic, mercury), total petroleum hydrocarbons (TPH), and naturally occurring radioactive materials (NORMs). Improper disposal of these wastes through open pit dumping, surface discharge, and landfarming facilitates contaminant migration into soil, surface water, and groundwater systems, exposing local populations through ingestion, inhalation, and dermal contact pathways.This review synthesizes current evidence on the environmental fate of drilling waste constituents, human exposure mechanisms, associated health outcomes, and governance frameworks relevant to oil producing communities globally, with particular reference to the Niger Delta region of Nigeria. Drawing on established theoretical frameworks—including Environmental Health Theory, the Source-Pathway-Receptor (SPR) model, Toxicology and Dose-Response Theory, and the Risk Assessment Paradigm—this review demonstrates that communities residing near drilling operations face significantly elevated risks of respiratory disorders, dermatological conditions, gastrointestinal illness, reproductive toxicity, neurotoxicity, and certain cancers. Risk characterization using Hazard Quotient (HQ), Hazard Index (HI), and Incremental Lifetime Cancer Risk (ILCR) metrics reveals that vulnerable subpopulations—children, pregnant women, farmers, and fishers—face disproportionate health burdens.The review identifies critical research gaps, including the lack of community-specific, multi-media environmental sampling linked to epidemiological health data; insufficient integration of mobility-based exposure modeling; and weak regulatory and institutional feedback loops that perpetuate hazardous disposal practices. Recommendations include strengthened multi stakeholder governance, adoption of sustainable waste management hierarchies, and interdisciplinary research integrating environmental toxicology, geospatial analysis, and clinical health assessment.